(untitled) (Neo Science Peer Reviewed Journal, 2024)
Language teaching as a communicative activity reveals the place of language in human life and society. Teaching the Karakalpak language in primary grades includes to develop students’ linguistic and language skills and educate the feeling of love for the language. This article discusses the improving the teaching of the Karakalpak language in primary classes of schools taught in other languages.